Assessing lung aeration using ultrasound after birth in near-term lambs at risk of respiratory distress - Pryor, E. J.; Davies, I. M.; Crossley, K. J.; Thiel, A. M.; McGillick, E. V.; Rodgers, K; Nitsos, I; Kitchen, M. J.; Blank, D. A.; Hooper, S. B. (Frontiers in Pediatrics, 2023)
Background: Optimizing respiratory support after birth requires real-time feedback on lung aeration. We hypothesized that lung ultrasound (LUS) can accurately monitor the extent and progression of lung aeration after birth and is closely associated with oxygenation. Methods: Near-term (140 days gestation, term ~147 days), spontaneously breathing lambs with normal (controls; n=10) or elevated lung liquid levels (EL; n=9) were delivered by Caesarean section and monitored for four hours after birth. LUS (Phillips CX50, L3-12 transducer) images and arterial blood gases were taken every 5-20 minutes. LUS images were analyzed both qualitatively (grading) and quantitatively (using the coefficient of variation of pixel intensity (CoV) to estimate the degree of lung aeration), which was correlated with the oxygen exchange capacity of the lungs (Alveolar-arterial difference in oxygen; AaDO2). Results: Lung aeration, measured using LUS, and the AaDO2 improved over the first 4 hours after birth. The increase in lung aeration measured using CoV of pixel intensity, but not LUS grade, was significantly reduced in EL lambs compared to controls (p=0.02). The gradual decrease in AaDO2 after birth was significantly correlated with increased lung aeration in both control (grade, r2 = 0.60, p<0.0001; CoV, r2 = 0.54, p<0.0001) and EL lambs (grade, r2 = 0.51, p<0.0001; CoV, r2 = 0.44, p<0.0001). Conclusions: LUS can monitor lung aeration and liquid clearance after birth in spontaneously breathing near-term lambs. Image analysis techniques (CoV) may be able detect small to moderate differences in lung aeration in conditions with lung liquid retention which are not readily identified using qualitative LUS grading.